2019
DOI: 10.1353/rhe.2019.0097
|View full text |Cite
|
Sign up to set email alerts
|

Raising the Stakes: Impacts of the Complete College Tennessee Act on Underserved Student Enrollment and Sub-Baccalaureate Credentials

Abstract: In 2010, Tennessee enacted the Complete College Tennessee Act (CCTA), which increased the proportion of state performance-based funding from 5.45% to 85% and added a 40% funding premium for progression and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 47 publications
1
31
0
Order By: Relevance
“…The authors found no evidence to suggest that PBF programs impacted total degree completions, first-to-second year retention, 6-year graduation rates, or bachelor’s degree completions. Similar findings have emerged in a host of quasi-experimental studies related to the impact of PBF on associate degree completion at community colleges in Ohio (Hillman et al, 2018), Washington (Hillman et al, 2015), and Tennessee (Hillman et al, 2018; Li & Ortagus, 2019). These single, or in some cases, few state studies provide strong evidence that PBF policies have had no impact on degree completion outcomes in a variety of state contexts.…”
Section: The Intended Outcomes Of Pbf Adoptionsupporting
confidence: 70%
See 3 more Smart Citations
“…The authors found no evidence to suggest that PBF programs impacted total degree completions, first-to-second year retention, 6-year graduation rates, or bachelor’s degree completions. Similar findings have emerged in a host of quasi-experimental studies related to the impact of PBF on associate degree completion at community colleges in Ohio (Hillman et al, 2018), Washington (Hillman et al, 2015), and Tennessee (Hillman et al, 2018; Li & Ortagus, 2019). These single, or in some cases, few state studies provide strong evidence that PBF policies have had no impact on degree completion outcomes in a variety of state contexts.…”
Section: The Intended Outcomes Of Pbf Adoptionsupporting
confidence: 70%
“…Several quasi-experimental studies have employed a DD regression approach and shown that PBF can lead to increases in the production of short-term certificates rather than associate degrees (Hillman et al, 2015, 2018; Hu, 2019; Li & Kennedy, 2018; Li & Ortagus, 2019). Hillman et al (2018) examined two of the most robust PBF-participating states, Tennessee and Ohio, and found that Tennessee community colleges responded to PBF by producing more certificates rather than longer-term associate or bachelor’s degrees.…”
Section: The Unintended Consequences Of Pbf Adoptionmentioning
confidence: 99%
See 2 more Smart Citations
“…In other words, within states that have a PF policy, colleges will act in ways aimed at improving performance because colleges are provided material incentives from the state (Dougherty and Hong 2006 ; Dougherty and Reddy 2013 ). Studies incorporating a resource dependency perspective typically suggest that colleges that rely more heavily on state appropriations (such as community colleges) will be more likely to engage in the desired behaviors of improving stated student outcomes (Hu 2019 ; Li and Ortagus 2019 ).…”
Section: Theoretical Logic Of Performance Fundingmentioning
confidence: 99%